The Meaning and Purpose of Primary Tooth Disposal Rituals: Implications for Pediatric Dental Professionals - Parsons, Clara L. B.; Mountain, Rebecca V.; Lau, Agnes; Troulis, Maria J.; Bidlack, Felicitas B.; Dunn, Erin C. (Frontiers in Dental Medicine, 2021)
Rituals for disposing of exfoliated primary teeth exist in virtually all cultures around the globe, suggesting an important psychological and social function for young children and parents. Despite the importance of these rituals, and the role they may play in children's interactions with dental professionals, the meaning and purpose of primary tooth disposal traditions has not yet received adequate attention in pediatric dentistry. The overarching goal of this perspective was to draw attention to the meaning and purpose of primary tooth disposal rituals and show how, with a greater understanding of these rituals, dental professionals could improve the interactions they have with their young patients. To achieve this goal, we first summarize findings from prior research on how primary tooth disposal rituals are primarily practiced as a rite-of-passage to ease the transition from early to later childhood, to counteract anxiety, trauma, or pain experienced by children of tooth-shedding age, and to honor spiritual or religious beliefs that are thought to protect the child and aid their healthy development. Second, we articulate how, by understanding the significance and diversity of these traditions, practitioners can potentially improve their ability to prevent dental anxiety, increase their cultural competence to engage with increasingly diverse pediatric patient populations, and ensure more timely primary oral care. Finally, we provide a two-pronged approach, centered around the pillars of Education and Communication, to improve overall patient care built on knowledge of these rituals and cultural practices.